Gambaran Nilai Hematokrit Metode Makrohematokrit Dengan Menggunakan Darah Vena Pada Penyakit Tuberkulosis Di Balai Besar Kesehatan Paru Masyarakat (Bbkpm) Makassar - jurnal syarif; Iga Ayuningsih (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2020)
This research is motivated by the desire of researchers to know the description of the hematocrit value in tuberculosis. The purpose of this study was to determine and determine the description of the hematocrit value of the macrohematocrit method using 10 samples of venous blood in tuberculosis. This study uses the macrohematocrit method and is presented in a quantitative descriptive form. Based on the results of research conducted on 10 samples of tuberculosis, it can be concluded that the hematocrit value below normal consists of 6 people and normal 4 people. For further researchers to be able to conduct research using automatic tools that are more sophisticated and have a smaller error rate and fast and accurate inspection time.